CLINICAL CHARACTERISTICS, HEMATOLOGICAL VARIATIONS AND BIOACCUMULATION OF HEAVY METALS IN BLOOD, HAIR AND URINE OF BREAST CANCER PATIENTS - Rimsha, Kinza Khalid, Navida, Muhammad Farhan, Muhammad Gulzada, Maryam Afzal, Yusra Iqbal, Anum Saleem, Fouzia Tanvir, Yasir Nawaz, Saba Munir, Khazina Rafee (Chelonian Research Foundation, 2024)
Breast cancer is an important reason of cancer related mortality in females, account for 15.0% of such fatalities. Hematological changes are frequently considered with disease. Research identified potential link between fluctuations in heavy metal metabolism and progression. This study aimed to evaluate clinical characteristics, hematological variations, and heavy metal accumulation in breast cancer patients. Data were gathered from Jinnah Hospital Lahore using a questionnaire designed to collect clinical information from patients. Participants provided informed consent before data collection. Blood, hair, and urine samples from both control and case groups were obtained and analyzed for hematological changes and metals accumulation. The study found average age of people was 48.9 years, with significant changes noted in stage III patients. Variations in ER, PR, and HER2 status were observed among patients. Significant differences were found across all age groups. The incidence of breast cancer was notably higher in Lahore compared to other cities. Hematological parameters differed significantly between control and affected individuals, and there were notable variations in metal concentrations across sample types. In summary, there was a higher incidence of invasive ductal carcinoma among females, particularly in Lahore and other urban areas. Significant variations in hematological parameters and heavy metal concentrations were observed, including lower iron levels in blood and hair and decreased zinc levels across all samples among cases play role in cancer Nickel levels are higher among cases but remain within safe limits, and lead levels were low, indicating lead may not be a significant factor in this study